Three kisses, one midnight : a novel - Chokshi, Roshani; Menon, Sandhya; Skye, Evelyn (Wednesday Books, 2022)
Three short stories come together to complete an opening setup in which three best friends and coven mates--Onny, Ash, and True--try to find true love on Halloween night, which also happens to be the date of their town's founding, and the night the Lady of Moon Ridge is said to leave the sky to visit their town. Using her grandmother's recipe, Onny Diamante concocts a love potion and gives her two friends a portion to use. Onny's hope is that it will lead her to her crush Alexander. But it's her lab partner, Byron, who seems to be getting in the way of the spell properly working. Shy Ash Lee hopes it will give him the courage to at least talk to Cassidy Rivera, even though they have nothing in common. Skeptic science buff True Tandon has no use for potions or relationships until she meets a ghost hunter she can't get off her mind.